The Evaluation of Machinability and Surface Texture of Tool Steel with Copper Electrode in Electro Discharge Machining - Mohd Daud, Mohd Ahadlin (2001)
The study reported in this thesis is a contribution towards the understanding on the relationship of Electro Discharge Machining (EDM) parameters in machining of tool steel. Some of the main parameters controlling material removal rate (MRR) in EDM, namely supply current, pulse on/off duration and electrode size with electrode wear rate (EWR) are studied and their effects on the machinability factors (MRR and EWR) are evaluated. The surface finish in term of surface texture, which determined by the roughness measurement on the machined surface (Ra) is also studied. Further, volumetric wear (VW) as the three-dimensional analysis among MRR, EWR and machining time or pulse on/off duration is analyzed. In the experiment using the die-sinking EDM, tool steel and copper were selected as the workpiece and electrode, respectively. Three sizes of copper electrode were used: diameter of 5 mm, 10 mm and 15 mm and two experimental setups were prepared. In setup-I, those electrodes were used to produce blind hole machining features at supply currents of 3A and 6A for machining time from 5 to 20 minutes, while pulse on/off duration was kept constant. In setup-2, machining time was kept constant, supply currents were also 3A and 6A but pulse on/off durations were varied from 6 to 12 J.1S. From the evaluation of MRR, EWR, surface roughness and VW, the results show that the electrode with diameter of 15 mm gives the best performance at all supply currents, machining time and pulse on/ofT durations. The values of MRR and EWR increase as the increasing of machining time, supply current and pulse on/off duration. Surface roughness has no relationship with machining time. In contrast, it has a close relationship with pulse on/off duration where the higher the pulse on/off duration the higher is the magnitude of surface roughness.